Effects of testosterone on leptin production in anterior pituitary cells of rats: An immunohistochemical study - Kus, I.; Colakoglu, N.; Ogeturk, M.; Kus, M. A.; Ozen, O. A.; Sarsilmaz, M. (Taylor & Francis Inc, 2007)
The aim of this study was to immunohistochemically examine the effects of orchidectomy and administration of testosterone hormone on leptin production in the rat anterior pituitary. Twenty-one male Wistar rats were divided into three groups. Group I and group II were designated as control (sham-orchidectomized) and orchidectomized rats, respectively. Rats in group III were orchidectomized and injected daily with testosterone propionate for 1 month. At the end of the experimental period, all animals were sacrificed by decapitation. The pituitary glands of all rats were removed and processed for semi- quantitative evaluation of immunohistochemical leptin staining. Intensity of immunostaining was determined on a scale between 0 (no staining) and 5 (heavy staining). Immunostaining of leptin was moderate (3+) in control rats, heavy (5+) in orchidectomized rats, and low (1+) in testosterone-treated orchidectomized rats, respectively. These findings indicate that orchidectomy increases leptin secretion in anterior pituitary cells, and this increase of leptin synthesis can be prevented by administration of testosterone propionate. Thus, testosterone seems to affect leptin production in the anterior pituitary of male rats.
Keywords: anterior pituitary; immunohistochemistry; leptin; rat; testosterone